2022
DOI: 10.3389/fmed.2022.859330
|View full text |Cite|
|
Sign up to set email alerts
|

JAK1/2 Inhibitor Baricitinib Improves Skin Fibrosis and Digital Ulcers in Systemic Sclerosis

Abstract: BackgroundSystemic sclerosis (SSc) is a rare disabling connective tissue disease with few available treatment options. Diffuse cutaneous systemic sclerosis (dcSSc) is associated with high mortality. A previous experiment has shown that JAK2 inhibitor can significantly improve skin fibrosis in bleomycin (BLM)-induced murine model, including reducing dermal thickening and collagen accumulation. We aimed to describe the efficacy of oral JAK1/2 inhibitor baricitinib in SSc patients, especially focusing on skin fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Our literature search retrieved seven articles that were published between 2018 and 2022. Of these, You et al [21] conducted a single-center, open-label clinical trial, Karalilova et al [22] conducted a pilot study, Hou et al [23] conducted a prospective observational study, and the remaining were case reports [24][25][26][27]. The extracted data were sparse and not complete because treatment with JAKinibs was mainly started for a cutaneous or an articular involvement.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our literature search retrieved seven articles that were published between 2018 and 2022. Of these, You et al [21] conducted a single-center, open-label clinical trial, Karalilova et al [22] conducted a pilot study, Hou et al [23] conducted a prospective observational study, and the remaining were case reports [24][25][26][27]. The extracted data were sparse and not complete because treatment with JAKinibs was mainly started for a cutaneous or an articular involvement.…”
Section: Resultsmentioning
confidence: 99%
“…At both follow ups, no new DU were reported. The mRSS of all nine patients that were evaluated at follow up improved more than 5 points, and 7 (77.78%) cases presented a decrease of more than 25% at week 24 [23].…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…75 Meanwhile, in a recent pilot study, the JAK1/2 inhibitor, baricitinib, was found to reduce skin fibrosis and digital ulceration in SSc patients. 76 The pharmacological effects of various JAK inhibitors differ depending on which specific cytokines are inhibited. Multiple JAK inhibitors that are currently being investigated in SSc studies, as well as their approved clinical utility for autoimmune diseases, route of administration, dosage, and safety profiles are listed in Table 3.…”
Section: Jak Inhib Iti On Is a P Otential Ther Apeuti C S Tr Ategymentioning
confidence: 99%
“…Peficitinib, a pan‐JAK inhibitor, reduces lymphocyte activation as well as cytokine and chemokine production in mononuclear cells and skin fibroblasts 75 . Meanwhile, in a recent pilot study, the JAK1/2 inhibitor, baricitinib, was found to reduce skin fibrosis and digital ulceration in SSc patients 76 …”
Section: Jak Inhibition Is a Potential Therapeutic Strategymentioning
confidence: 99%